Impact of resection margin status on recurrence and survival in patients with resectable, borderline resectable, and locally advanced pancreatic cancer - Rompen, Ingmar F.; Marchetti, Alessio; Levine, Jonah; Swett, Benjamin; Galimberti, Veronica; Han, Jane; Riachi, Mansour E.; Habib, Joseph R.; Imam, Rami; Kaplan, Brian; Sacks, Greg D.; Cao, Wenqing; et al. (Surgery, 2025)
Background - To improve outcomes for patients with pancreatic ductal adenocarcinoma, a complete resection is crucial. However, evidence regarding the impact of microscopically positive surgical margins (R1) on recurrence is conflicting due to varying definitions and limited populations of patients with borderline-resectable and locally advanced pancreatic cancer. Therefore, we aimed to determine the impact of the resection margin status on recurrence and survival in patients with pancreatic ductal adenocarcinoma stratified by local tumor stage. - Methods - We performed a retrospective cohort study on patients with nonmetastatic pancreatic ductal adenocarcinoma undergoing pancreatectomy at a high-volume academic center (2012-2022). R1 was subclassified into microscopic invasion of the margin (R1 direct) or carcinoma present within 1 mm but not directly involving the margin (R1 <1 mm). Overall survival and time to recurrence were assessed by log-rank test and multivariable Cox regression. - Results - Of 472 included patients, 154 (33%) had an R1 resection. Of those 50 (32%) had R1 <1 mm and 104 (68%) R1 direct. The most commonly involved margin was the uncinate (41%) followed by the pancreatic neck (16%) and vascular margins (9%). Overall, a stepwise shortening of time to recurrence and overall survival was observed with an increasing degree of margin involvement (median time to recurrence: R0 39.3 months, R1 <1 mm 16.0 months, and R1 direct 13.4 months, all comparisons P < .05). Multivariable analyses confirmed the independent prognostic value of R1 direct across all surgical stages. - Conclusion - The resection margin status portends an independent prognostic value. Moreover, this association persists in patients with borderline-resectable and locally advanced pancreatic cancer. Increasing the R0-resection rate is the most important potentially influenceable prognostic factor for improving surgery-related outcomes.
Gesehen am 28.07.2025